Sumber Pendapatan Negara dan Alokasi Belanjanya dalam Konteks Keuangan Publik Islam Era Kekinian di Brunei Darussalam - Riska Octavia Habie (Scimadly Publishing, 2023)
This research is to review the income and financial allocation of Brunei Darussalam in the context of modern Islamic public finance. The research method uses descriptions from various references, then summarized to get the desired results. The results explain that the State of Brunei Darussalam is located in the Southeast Asia region and has abundant natural resources in the form of oil, natural gas, silica sand, forests and marine resources. The country's main source of income comes from exports of oil and natural gas, therefore this country has high exports, which account for more than 90% of the total. In addition, in general, the country's income in the Islamic public financial sector comes from zakat and waqf funds whose management of funds is under the Brunei Islamic Council of Ugama (MUIB). This paper focuses on sources of income and expenditure allocation in the context of Islamic public finance in Brunei Darussalam.